The Relationship Between Distance To Health Facilities And Regularity Of Pregnancy Check-Ups (Anc) In Remote Areas - Hasrianti Hasrianti; Rasdiana Rasdiana; Cakrawati R (International Journal of Health Sciences, 2025)
Access to maternal health services is a determining factor in the success of maternal and child health programs. One important indicator is the regularity of antenatal care ( ANC ) visits, which is significantly influenced by geographic conditions, including distance to health facilities. This study aims to analyze the relationship between distance to health facilities and the regularity of antenatal care visits among pregnant women in remote areas. The study used an observational analytical design with a cross-sectional approach. Sectional. The research population was all pregnant women in the working area of Health Center X, totaling 120 people, and the sample consisted of 80 respondents taken proportionally. Random sampling. Primary data were collected through interviews using a structured questionnaire, while secondary data were obtained from the KIA book and community health center reports. Data analysis was performed univariately and bivariately using the Chi- Square (χ²) test with a 95% confidence level. The results showed that 62.5% of respondents traveled >5 km to a health facility, and 58.7% did not undergo regular ANC check-ups. Statistical tests showed a p-value of 0.002 (<0.05), indicating a significant relationship between distance traveled and the regularity of prenatal check-ups. The longer the distance traveled, the lower the frequency of ANC visits. In conclusion, difficult geographic access is a significant determinant of irregular antenatal care in remote areas. It is recommended that the government and health facilities expand the reach of maternal services through mobile services, the role of village midwives, and integrated integrated health posts (Posyandu) to improve the accessibility and regularity of ANC.